A Case Series of Very Late-Onset Schizophrenia-like Psychosis - Prabhu, Swathi; Pujar, Lavanya; Chako, Jayin Thekkinadath; YR, Niranjan (Nepal Journal of Neuroscience, 2024)
The onset of Schizophrenia in men is usually in late adolescence and early twenties and in women in late twenties and early thirties. However, in very rare conditions it is observed that Schizophrenia is seen in patients above 60 years of age. In such cases, the diagnosis of very late onset Schizophrenia like Psychosis (VLOSLP) is made.The precise nature of VLOSLP still poses uncertainties, as it is unclear whether it is a unique disorder, a potential precursor to dementia, or an entirely different condition that remains elusive. More extensive research is necessary to explore this avenue and delve deeper into the subject matter.The use of low-dose atypical antipsychotics is commonly advised, with careful monitoring for any potential side effects. It is essential to provide comprehensive psychoeducation to both the patient and their family members to enhance treatment adherence.